Agglutination of Platelet-Type von Willebrand’s Disease Platelets by Bovine von Willebrand Factor - Takahashi, Hoyu; Shibata, Akira (Thrombosis and Haemostasis, 1985)
It has been shown that platelets from patients with platelet- type von Willebrand’s disease (vWD) agglutinate upon the addition of human von Willebrand factor (vWF) in the absence of ristocetin or botrocetin, suggesting that platelet membrane receptors for human vWF is abnormal. The present work reports the platelet agglutinability on stimulation with bovine vWF in platelet-type vWD. Platelets in patient platelet-rich plasma or washed platelet suspensions and patient platelets treated with formalin agglutinated in the presence of markedly lower concentrations of bovine vWF than those required for normal platelets. This finding provides additional evidence that platelet-type vWD platelets have abnormal expression of binding sites for vWF on their surface, and supports that platelet receptors for bovine vWF are identical or very close to those for human vWF.
Keywords: Platelet-type von Willebrand’s disease; von Willebrand factor; Bovine von Willebrand factor; Platelet agglutination; Receptor